MOTIVANDO ADOLESCENTES À CRIAR APLICATIVOS MOBILE - Buchholz, Daniel; Schulze, Vinicios Dutra; Jung, Inez Zagula; Rodrigues, Mauro Fonseca; Cavalheiro, Marcos Ronaldo Melo (Salão do Conhecimento, 2019)
Projeto de Extensão, do Grupo Programe o seu Futuro.